Legacy and Emerging Pollutants and Their Effects Through the Lens of Environmental Management - Christina Emmanouil; Petros Samaras; Dorothea Kassiteropoulou (Journal of Xenobiotics)
In the quest for worldwide economic development, the principles of sustainable development that involve social justice and efficient environmental protection are sometimes forgotten [...]